Application of Logan Avenue Problem Solving - Heuristic Learning Model with Inductive Strategy to Increase Interest and Accounting Learning Outcomes of Class Xii Accounting Students at Smk Negeri 7 Medan Tp. 2018/2019 - Mahdi Rahmad (Outline Publisher, 2022)
The problem in this research is the low interest and learning outcomes of accounting students in Class XII Accounting at SMK Negeri 7 Medan. The purpose of this study was to determine the increase in interest and learning outcomes of accounting students of class XII Accounting at SMK Negeri 7 Medan Swasta TP. 2018/2019 through the application of the Logan Avenue Problem Solving - Heuristic learning model with an Inductive Strategy. This type of research is Classroom Action Research (CAR). The results of giving an interest questionnaire obtained the results of student interest in the first cycle there were students who had high learning interest as many as 3 students ( 8.11%, moderate interest as many as 30 students (81.08%) and low interest as many as 4 students (10.81%) and no students (0%) for not being interested and experiencing an increase in cycle II as many as 29 students (78.38%) who have high interest, and moderate interest as many as 8 students (21.62%) and 0 students or (0%) for students who have low interest and are not interested. From the results of data analysis, it was obtained that the learning outcomes test data with an average value obtained from the pre-test 57.38 with students who completed 13 students (35.14%) and the post-test cycle I with an average value of 71.08 with students 29 students (78.38%) completed and the post-test results increased in cycle II with an average score of 85.62 with 34 students (91.89%).